Forever becoming : the ever deepening realization of Presence in my life - Franck, Vivian (Bloomington, Ind Balboa Press, 2014)
Describes the author's youth in an all-Catholic northern Maine town, her life as a nun in various Orders, and her subsequent experiences after leaving the convent.
Includes bibliographical references.
Maine author.
Keywords: Franck, Vivian; Franck, Vivian -- Religion; Nuns -- Biography; Ex-nuns -- Maine -- Biography; Christian life